Application of Simplicillium chinense for Cd and Pb biosorption and enhancing heavy metal phytoremediation of soils - Jin, Zhongmin; Deng, Songqiang; Wen, Yuchen; Jin, Yifeng; Pan, Lin; Zhang, Yanfu; Black, Tom; Jones, Kevin C.; Zhang, Hao; Zhang, Dayi (The Science of the total environment, 2019)
Phytoremediation is an effective approach to control soil heavy metal pollution. This study isolated a fungus strain from soils contaminated by cadmium (Cd) and lead (Pb) in Zhalong Wetland (China), which was identified as Simplicillium chinense QD10 via both genotypic and phenotypic analysis. The performance and mechanism of S. chinense QD10 in Cd and Pb adsorption was unraveled by morphological analysis and biosorption test, and its roles in ameliorating phytoremediation by Phragmites communis were tested in pot-experiments. Cd biosorption was attributed to the formation of Cd-chelate, whereas Pb was predominantly adsorbed by extracellular polymeric substances. Metal biosorption followed Langmuir isotherm, and the maximum biosorption capacity was 88.5 and 57.8 g/kg for Cd and Pb, respectively. Colonized in soils, such biosorption behavior of S. chinense QD10 can generate gradients of available Cr or Pb and drive their enrichment. Accordingly, S. chinense QD10 amendment significantly enhanced the phytoextraction of Cd and Pb by P. communis, possibly attributing to rhizospheric enrichment of Cd or Pb and defending effects on plants, explained by the significant removal of acid-extractable and reducible metals in soils and the increase of Cd and Pb content in P. communis tissues. The present study explored the mechanisms of S. chinense QD10 in Cd and Pb biosorption and proved its potential in ameliorating the phytoremediation performance at metal contaminated sites. [Display omitted] •First study on metal biosorption capability of fungus Simplicillium chinense•Difference in Cd and Pb biosorption mechanisms by Simplicillium chinense•28.6–48.0% more metal removal from soils via fungi-mediated phytoremediation•Rhizosphere-fungi interaction explains the enhanced phytoremediation performance.